The system of administrative legal backer-ups of rights and freedoms of persons is with disability in the field of labor activity - Kondratenko, Vitalii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
Kinds are analysed administrative legal backer-ups of rights and freedoms of persons with disability in the field of labor activity. Drawn conclusion that in our state repressing amount of the indicated category of people does not have permanent employment that predefined ineffectiveness of separate from the indicated legal facilities, concrete legislative changes are offered in relation to the improvement of this situation.